Study of the mechanical performance and analysis of hybrid natural snake grass-jute-glass fiber strengthened polyester composite - Thiruvasagam, C.; Prabagaran, S.; Suresh, P. (International Journal of Engineering and Technology, 2017)
The research paper involves fiber composites form a special category materials that are contributing to present swaping of manufactured Â hybrid Â which finds traditional and non traditional applications. The study explains which are accentuates and optimizing for the recently recognized snake grass standard materials. In this article, the prospecting performance characterization of SG fiber is selected and contrasted as per the ASTM standard. This study additionally manages the examination apply different phenomena of this stages in Jute and snake as fortifications utilized index ended a try. Experiments have been conducted on normal Filaments, snake grass, Glass Fiber and Jute to analyse their Mechanical properties. The common strands are orchestrated in the flat and vertical heading as transferred quality on all sides. Microstructural analysis of these hybrid composite is observed using ScanningÂ Electron Microscope that reveals bonding and Filament breaksge, Voids and Fiber decover which are further investigated.